Determining Marketing Strategies Using Swot and 4P in The Sanjaiku Chips Business - Hidayat Hidayat; Akhmad Wasiur Rizqi; Awaludin Iqbal Iqbal (Jurnal Serambi Engineering, 2023)
Keripik Sanjaiku is a new home industry specializing in the snack food sector, namely cassava chips. This study aims to detail the marketing strategy of this product by applying the 4P method, namely product, price, place, and packaging, before establishing concrete marketing steps. The researcher conducted a SWOT (strengths, weaknesses, opportunities, threats) analysis to identify internal and external factors that could affect the marketing strategy. The results of the SWOT analysis showed that weaknesses, especially related to the absence of a halal label, lack of promotion and points of sale, and lack of utilization of information technology, have a significant impact on consumer confidence in Sanjaiku products. Based on the findings of the SWOT analysis, it can be concluded that the use of the 4P marketing strategy would be beneficial for Sanjaiku business owners. The recommended steps include the addition of a halal label to build consumer trust, the implementation of more intensive and attractive promotions on social media platforms such as Instagram to reach far-flung consumers, and the utilization of technology to simplify the ordering process and improve production efficiency so that consumer waiting time can be minimized.